2020
DOI: 10.3847/1538-4357/ab5d2d
|View full text |Cite
|
Sign up to set email alerts
|

The 1.28 GHz MeerKAT DEEP2 Image

Abstract: We present the confusion-limited 1.28 GHz MeerKAT DEEP2 image covering one q » ¢ 68 FWHM b Unified Astronomy Thesaurus concepts: Radio telescopes (1360); Galaxy counts (588); Star formation (1569)

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(84 citation statements)
references
References 45 publications
6
73
0
Order By: Relevance
“…the actual source distribution is in excess of the predictions by TGSS survey at lower flux range. Similar findings have been recently reported at a higher frequency of the 1.28 GHz MeerKAT DEEP2 Image where Mauch et al (2020) found that the model prediction lies significantly below the observed source counts at low flux range. At lower range, we find that the values of the measured C after point source subtraction decrease with increasing and shows a power-law like behaviour (at 7 http://www.physics.iisc.ernet.in/~nroy/plot_html < 700).…”
Section: Resultssupporting
confidence: 91%
“…the actual source distribution is in excess of the predictions by TGSS survey at lower flux range. Similar findings have been recently reported at a higher frequency of the 1.28 GHz MeerKAT DEEP2 Image where Mauch et al (2020) found that the model prediction lies significantly below the observed source counts at low flux range. At lower range, we find that the values of the measured C after point source subtraction decrease with increasing and shows a power-law like behaviour (at 7 http://www.physics.iisc.ernet.in/~nroy/plot_html < 700).…”
Section: Resultssupporting
confidence: 91%
“…MeerKAT (Jonas & MeerKAT Team 2016;Camilo et al 2018;Mauch et al 2020) is an array made of 64 13.5 m antennas located in Northern Cape, South Africa. Its spatial resolution is around 5″.…”
Section: Radio Observations With Vla and Meerkatmentioning
confidence: 99%
“…This illustrates that an equivalent survey would not i Karoo Array Telescope. j See Mauch et al (2020) for further technical details. k For MeerKAT sensitivity calculations, see the online sensitivity calculator provided by the South African Radio Astronomy Observatory, based on real observations: https://archive-gw-1.kat.ac.za/public/tools/continuum_sensitivity_calculator.html l https://github.com/ratt-ru/simms.…”
Section: Askap and Meerkat Within The Context Of All-sky Surveysmentioning
confidence: 99%